Comprehensive evaluation of the linear stability of Alfvén eigenmodes driven by alpha particles in an ITER baseline scenario. (15th June 2016) - Figueiredo, A.C.A.; Rodrigues, P.; Borba, D.; Coelho, R.; Fazendeiro, L.; Ferreira, J.; Loureiro, N.F.; Nabais, F.; Pinches, S.D.; Polevoi, A.R.; Sharapov, S.E.
Abstract: The linear stability of Alfvén eigenmodes in the presence of fusion-born alpha particles is thoroughly assessed for two variants of an ITER baseline scenario, which differ significantly in their core and pedestal temperatures. A systematic approach based on CASTOR-K (Borba and Kerner 1999 J. Comput. Phys . 153 101; Nabais et al 2015 Plasma Sci. Technol . 17 89) is used that considers all possible eigenmodes for a given magnetic equilibrium and determines their growth rates due to alpha-particle drive and Landau damping on fuel ions, helium ashes and electrons. It is found that the fastest growing instabilities in the aforementioned ITER scenario are core-localized, low-shear toroidal Alfvén eigenmodes. The largest growth-rates occur in the scenario variant with higher core temperatures, which has the highest alpha-particle density and density gradient, for eigenmodes with toroidal mode numbers n ≈ 30 . Although these eigenmodes suffer significant radiative damping, which is also evaluated, their growth rates remain larger than those of the most unstable eigenmodes found in the variant of the ITER baseline scenario with lower core temperatures, which have n ≈ 15 and are not affected by radiative damping.